2019
DOI: 10.3389/fimmu.2019.02449
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-378a-3p by Inflammation Enhances IL-33 Levels: A Novel Mechanism of Alarmin Modulation in Ulcerative Colitis

Abstract: Ulcerative colitis (UC) is an inflammatory bowel disease (IBD) characterized by mucosa damage associated with an uncontrolled inflammatory response. This immunological impairment leads to altered inflammatory mediators such as IL-33, which is shown to increase in the mucosa of active UC (aUC) patients. MicroRNAs present a distorted feature in inflamed colonic mucosa and are potential IL-33 regulating candidates in UC. Therefore, we studied the microRNA and mRNA profiles in inflamed colonic samples of UC patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 66 publications
(78 reference statements)
2
32
0
Order By: Relevance
“…For miR over-expression assays we used the pGPGLenti-human cytomegalovirus-green fluorescent protein (CMV-GFP)-puro vector, previously validated for microRNA expression [ 83 ]. After amplification of the primiR-145 sequence (300 pb flanking the miR-145 stemloop: MI0000461), this insert was cloned in the SalI site in forward sense (pGPG-145).…”
Section: Methodsmentioning
confidence: 99%
“…For miR over-expression assays we used the pGPGLenti-human cytomegalovirus-green fluorescent protein (CMV-GFP)-puro vector, previously validated for microRNA expression [ 83 ]. After amplification of the primiR-145 sequence (300 pb flanking the miR-145 stemloop: MI0000461), this insert was cloned in the SalI site in forward sense (pGPG-145).…”
Section: Methodsmentioning
confidence: 99%
“…To help users navigate the miRNA information in the literature, emiRIT just captures terms about cellular processes and verifies if the terms correspond to any GO term using exact string matching. For example, the UCL annotations for miR-378a-3p included involvement in the negative regulation of cytokine production involved in inflammatory response (GO:1900016) with evidence from PMID:31824476 ( 70 ). From this abstract, emiRIT extracts the mention of IL-33 being a target of miR-378.…”
Section: Resultsmentioning
confidence: 99%
“…The miR-378 family has not been reported in studies of GD patients, but was reported by Shi Haizhong et al [18]. It is suggested that the low expression of the miR-378 family enhanced the levels of its downstream molecule IL-33 and played a role in the proin ammatory response of the autoimmune disease ulcerative colitis (UC).…”
Section: Discussionmentioning
confidence: 99%